The Influence of Email on Language Learning A Positive Impact - Sabieh, Christine ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2002)
This study investigated the influence of e-mail on English language learning among college freshmen enrolled in a remedial English class. English was considered the first or second foreign language for all participants. Students were divided into two groups. One group was allowed face to face communication in class and during office hours with the educator, while the other was allowed face to face communication in class and e-mail communication outside of class with the educator. The researcher analyzed frequency and content of communication, address style, long-term communication, and communication dynamics. By using e-mail, students became empowered learners who were active, responsible, and motivated to communicate to enhance their language learning. As active learners, they could create and edit a message, then send it at their own pace. They expected to receive feedback but were not anxious because it took place in a nonthreatening, nonjudgemental environment. Peer pressure and modeling were minimal in the e-mail condition. The non-e-mail group felt more peer pressure and lack of privacy, and they tended to be more passive learners. The presence of others (in the classroom or the educators office) influenced students perceptions, evaluation, and behavior. Tables and figures are appended. (Contains 44 references.) (SM)
ERIC Note: Paper presented at the Annual Center for Developing English Language Teaching Symposium (22nd, Cairo, Egypt, April 22-24, 2002).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; Computer Uses in Education; Electronic Mail; English (Second Language); Feedback; Foreign Countries; Higher Education; Interpersonal Communication; Second Language Instruction; Teacher Student Relationship; Teaching Methods; Lebanon; Reports, Research; Speeches/Meeting Papers